A novel autosomal recessive GJB2‐associated disorder: Ichthyosis follicularis, bilateral severe sensorineural hearing loss, and punctate palmoplantar keratoderma. Issue 2 (1st December 2018) - Youssefian, Leila; Vahidnezhad, Hassan; Saeidian, Amir Hossein; Mahmoudi, Hamidreza; Karamzadeh, Razieh; Kariminejad, Ariana; Huang, Jianhe; Li, Leping; Jannace, Thomas F.; Fortina, Paolo; Zeinali, Sirous; White, Thomas W.; et al.
Abstract: Ichthyosis follicularis, a distinct cutaneous entity reported in combination with atrichia, and photophobia has been associated with mutations in MBTPS2 . We sought the genetic cause of a novel syndrome of ichthyosis follicularis, bilateral severe sensorineural hearing loss and punctate palmoplantar keratoderma in two families. We performed whole exome sequencing on three patients from two families. The pathogenicity and consequences of mutations were studied in the Xenopus oocyte expression system and by molecular modeling analysis. Compound heterozygous mutations in the GJB2 gene were discovered: a pathogenic c.526A>G; p.Asn176Asp, and a common frameshift mutation, c.35delG; p.Gly12Valfs*2. The p.Asn176Asp missense mutation was demonstrated to significantly reduce the cell–cell gap junction channel activity and increase the nonjunctional hemichannel activity in the Xenopus oocyte expression system. Molecular modeling analyses of the mutant Cx26 protein revealed significant changes in the structural characteristics and electrostatic potential of the Cx26, either in hemichannel or gap junction conformation. Thus, association of a new syndrome of an autosomal recessive disorder of ichthyosis follicularis, bilateral severe sensorineural hearing loss and punctate palmoplantar keratoderma with mutations in GJB2, expands the phenotypic spectrum of the GJB2 ‐associated disorders. The findings attest to the complexity of the clinical consequences of different mutations in GJB2 . Abstract : In two families, the genetic cause of a novel syndrome of ichthyosis follicularis, bilateral severe sensorineural hearing loss, and punctate palmoplantar keratoderma was investigated by whole‐exome sequencing, and recessive mutations in the GJB2 were found. The mutation was demonstrated to significantly change the cell‐cell gap junction channel and hemichannel activities in the Xenopus oocyte expression system. Molecular modeling analyses revealed significant changes in the structural characteristics and electrostatic potential of the connexin 26, either in hemichannel or gap junction conformation.